VAR model for regional logistics prediction. (19th May 2018) - Feng, Shouhua
Abstract: The development of regional logistics expands the wholesale and retail trade market. The demand for logistics produced by wholesale and retail trade directly drives the development of regional logistics. This paper selects six indicators of logistics demand, logistics supply, GDP and so on. Using ADF test, VAR model and Granger causality test, we establish a model equation of regional logistics and wholesale and retail trade with good fitting degree. Finally, it puts forward some policies and suggestions such as establishing an integrated transport network and promoting logistics information engineering.